Pengaruh Pelatihan, Gaya Kepemimpinan, Dan Beban Kerja Terhadap Produktivitas Kerja Karyawan - Alia Oktaviani; Odang Kusmayadi (LPPM Universitas Buddhi Dharma, 2025)
In an era of increasingly fierce global competition, enhancing employee work productivity has become a crucial factor determining an organization's success in achieving its goals. Employee productivity is influenced by various complex and interrelated factors, including the training provided, leadership style applied, and workload imposed. This study aims to comprehensively analyze the influence of these three factors on employee work productivity. Using a systematic literature review (SLR) approach, this study examined various scientific journals discussing the relationship between training, leadership, and workload on employee productivity. The literature search process was conducted through several leading journal databases such as Scopus, Science Direct, Google Scholar, JSTOR, and Emerald Insight using specific keywords related to research variables. The analysis results show that effective training programs significantly improve employee skills and competencies, enabling them to complete tasks more effectively and efficiently. Training is not limited to conventional technical skills but also includes digital literacy and adaptability to evolving technologies. Appropriate leadership styles, particularly transformational and participatory, have been proven to increase employee motivation and job satisfaction, ultimately positively impacting productivity. Leaders who can inspire, motivate, and empower employees tend to create a conducive work environment where employees feel valued and motivated to deliver their best performance. Optimal workload management contributes to maintaining work-life balance and reducing stress, with the relationship between workload and performance not necessarily linear and simple, but involving complex psychological processes. These findings confirm that these three factors have a significant influence on employee work productivity, both individually and simultaneously. In the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era and digital transformation, the interaction between these three factors becomes increasingly important to consider in creating organizational resilience. The dimension of organizational culture is also an important moderating factor in the relationship between training, leadership style, workload, and productivity. The practical implication of this research is the need for organizations to adopt a more integrated and contextual approach to improving employee work productivity, by designing strategic policies that align training programs, leadership development, and workload management within a cohesive organizational cultural framework to optimize human resource performance.